Cultivar relationships in mango based on fruit volatile profiles - Pandit, Sagar S.; Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2009)
Aroma volatiles of mango (Mangifera indica L.) determine consumer acceptability and influence selection, whilst breeding. To assess their variety, composition and possible impact on cultivar relationships, volatile blends of 22 Indian and five non-Indian cultivars were investigated using solvent extraction and gas chromatography. Totally 84 volatiles belonging to various chemical classes were detected. Based on the Cumulative Occurrence of members of these classes, cultivars were grouped as monoterpene or sesquiterpene dominant. a-Pinene, beta-myrcene and beta-caryophyllene were found in all 27 cultivars. For ordination, common compounds with high (relative) concentration provided quantitative characters, whereas the rare and lesser ones provided qualitative (binary) characters; non-Indian cultivars separated from Indian ones but displayed close relations within their groups. In conclusion, mango flavour is dominated qualitatively as well as quantitatively by terpene hydrocarbons; ancient selection of mango cultivars is hinted to be driven by different aroma characters in different parts of the world. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Flavour; GC-MS; Mangifera indica; Multivariate analysis; Ordination

Spatial and temporal changes in the volatile profile of alphonso mango upon exogenous ethylene treatment - Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2013)
Alphonso is a highly favoured and exported mango cultivar among the vast mango germplasm of India. Being a climacteric fruit, ethylene plays an important role in ripening of mango. For deeper understanding of effect of pre-climacteric ethylene treatment on volatile profiles of Alphonso mango, 26 volatiles were tracked through six ripening stages of pulp and skin of ethylene-treated and control Alphonso fruits. The study revealed accelerated ripening in terms of early appearance of ripening-specific compounds, lactones and mesifuran, upon ethylene treatment. While the level of lactones remained unaffected, the mesifuran level vastly increased upon ethylene treatment. Skin showed high terpene content while pulp had higher amount of lactones compared to skin. This work points towards involvement of ethylene as a natural hormone in the biosynthesis of lactones and furanones in naturally ripened fruits; whereas, an increase in the terpene level during ripening appears to be independent of ethylene. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ethylene; Flavour; Mango; Pre-climacteric; Ripening; Volatiles

Molecular cloning and characterization of O-methyltransferase from mango fruit (mangifera indica cv. alphonso) - Chidley, Hemangi G.; Oak, Pranjali S.; Deshpande, Ashish B.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Molecular Biotechnology, 2016)
Flavour of ripe Alphonso mango is invariably dominated by the de novo appearance of lactones and furanones during ripening. Of these, furanones comprising furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone) are of particular importance due to their sweet, fruity caramel-like flavour characters and low odour detection thresholds. We isolated a 1056 bp complete open reading frame of a cDNA encoding S-adenosyl-l-methionine-dependent O-methyltransferase from Alphonso mango. The recombinantly expressed enzyme, MiOMTS showed substrate specificity towards furaneol and protocatechuic aldehyde synthesizing mesifuran and vanillin, respectively, in an in vitro assay reaction. A semi-quantitative PCR analysis showed fruit-specific expression of MiOMTS transcripts. Quantitative real-time PCR displayed ripening-related expression pattern of MiOMTS in both pulp and skin of Alphonso mango. Also, early and significantly enhanced accumulation of its transcripts was detected in pulp and skin of ethylene-treated fruits. Ripening-related and fruit-specific expression profile of MiOMTS and substrate specificity towards furaneol is a suggestive of its involvement in the synthesis of mesifuran in Alphonso mango. Moreover, a significant trigger in the expression of MiOMTS transcripts in ethylene-treated fruits point towards the transcriptional regulation of mesifuran biosynthesis by ethylene.
Keywords: Ethylene; expression; Flavour; Mango; Mesifuran; Ripening